Integrating the UN SDGs into WTO Law. - Zhao, Xinyan (Springer, 2025)
Sustainable development is so important that humanity must do its utmost to achieve these goals for the well-being of the present and future generations. WTO members have started to reform WTO rules since the WTO's Buenos Aires Ministerial Conference in 2017. The book describes a possible bright future for readers: WTO members can integrate the UN SDGs into WTO law (i.e., create sustainable trade rules) by establishing a sustainable development club and constitutionalising the WTO.
Keywords: World Trade Organization.; Sustainable development -- Law and legislation.; Electronic books.